Quaderni di Studi Arabi (JSTOR)
Quaderni di Studi Arabi was founded by professor and academics of the University of Venice in 1983 with a special issue in honour of the doyen of Italian Arabic studies, Francesco Gabrieli. Its main field of study was and is the Arab civilization in its historical and cultural dimensions. A New Series of the Quaderni di Studi Arabi, published by the Istituto per l?Oriente C.A. Nallino in Rome, started in 2006 and consists in yearly issues that include a monographic section by a major specialist, a more general section, and a final section of short notices and reviews. Among the topics that have been already discussed and those that are planned for the coming issues there are: folk poetry, locations and the imaginary in Arabic literature, historical methodology, poetry by knights and bandits, medieval Arabic encyclopaedias, Arabic theatre, Moslem Sicily, and archaeology in the Arab countries.
Keywords: African Studies